A General Iteration Formula of VIM for Fractional Heat- and Wave-Like Equations. (27th March 2013) - Yin, Fukang; Song, Junqiang; Cao, Xiaoqun
Abstract : A general iteration formula of variational iteration method (VIM) for fractional heat- and wave-like equations with variable coefficients is derived. Compared with previous work, the Lagrange multiplier of the method is identified in a more accurate way by employing Laplace's transform of fractional order. The fractional derivative is considered in Jumarie's sense. The results are more accurate than those obtained by classical VIM and the same as ADM. It is shown that the proposed iteration formula is efficient and simple.